Theoretical Basis of Using the Electronic Learning Environment in the Educational Process - Zakirjanovich, Khudaiberdiev Mansur (European Journal of Life Safety and Stability (2660-9630), 2024)
In this article, are revealed the specific features of the electronic learning environment, the development of educational resources using electronic learning technologies that allow providing high-quality information and teaching-methodical support to the process of increasing educational efficiency ways and possibilities of gathering, systematization, storage and its usage.